(untitled) (The Pakistan Development Review, 1998)
Trade is a field of economics that is useful for investigating the issue of economic competitiveness. A nation’s advantages in competing against other nations are reflected in its performance in international economic transactions. Earlier theories on trade (Ricardian and Heckscher-Ohlin) analysed a nation’s inter-sectoral comparative advantage. Due to the intuitive appeal of these theories, governments have implemented various policies designed to improve comparative advantage in factor costs by reducing interest rates and resorting to devaluation, special depreciation allowances, export financing, etc. There is now a growing awareness that these theories are unrealistic as to many industries, although they can be useful in explaining broad tendencies apparent in the patterns of trade.